Structural comparison of two ferritins from the marine invertebrate Phascolosoma esculenta. Issue 3 (28th February 2021) - Ming, Tinghong; Huan, Hengshang; Su, Chang; Huo, Chunheng; Wu, Yan; Jiang, Qinqin; Qiu, Xiaoting; Lu, Chenyang; Zhou, Jun; Li, Ye; Su, Xiurong
Abstract : For marine invertebrates with no adaptive immune system, ferritin is a major intracellular iron‐storage protein with a critical role in innate immunity. Here, we present the crystal structures of two novel ferritins [Fer147 and Phascolosoma esculenta ferritin (PeFer)] from the marine invertebrate P. esculenta, which resides in muddy‐bottom coastal regions. Fer147 and PeFer exhibit the 4‐3‐2 symmetry of cage‐like hollow shells containing 24 subunits, similar to other known ferritins. Fer147 and PeFer contain both the conserved ferroxidase center and threefold channels. Subtle structural differences in the putative nucleation sites suggest possible routes of metal ion movement in the protein shells. However, the marked variation in the electrostatic potential of the threefold channels in Fer147 and the fourfold channels in PeFer suggests significant diversity between Fer147 and PeFer in terms of metal ion aggregation and cation exclusion. In summary, the presented crystal structures may serve as references for studies of the iron‐storage mechanism of additional ferritins from marine invertebrates. Abstract : In this study, we present the crystal structures of two novel ferritins from the marine invertebrate Phascolosoma esculenta, which resides in muddy‐bottom coastal regions. They contain both the conserved ferroxidase center and 3‐fold channels, but exhibit marked variation in the electrostatic potential of the 3‐fold channels in Fer147 and the 4‐fold channels in PeFer.